Private-Sector Financial Liabilities in Advanced Economies : Is More Better? - Tang, Man-Keung (IMF Working Papers; Working Paper, 2007)
Advanced economies have been experiencing diverse developments in accumulation of financial liabilities by their household and corporate sectors since around 1995. Crosscountry- industry evidence indicates that the type of the financial system and the degree of labor market flexibility matter for the economic impact of expanded borrowings. Especially in countries with a more arm's length-based financial system and less rigid labor market, faster creation of corporate liabilities in recent years appears to have spurred growth of industries more reliant on external finance, and strengthened the development of growing industries. The findings suggest an association of recent increases in corporate borrowings with a reduction in costs of external finance and improvement in resource allocation-two supposed channels through which finance facilitates growth.